The twilight of the idols, Nietzsche and the need for educators - Toledo Gutierrez, Carlos (2021)
In the prologue to the book Twilight of the idols (1888), Nietzsche writes: “This writing too —the title gives it away— is above all a respite, a place in the sun, a getaway to the idleness of a psychologist” (2016, p. 618). And later, in another reflection presented in the book, he affirms: “Educators are needed who are themselves educated” (2016, p. 652). These two quotes are the starting point to reflect on education in Peru from a critical perspective, about its problems and possibilities. We propose that there is a pseudo-crisis of education, without educators, since regular basic education teachers identify themselves as professors or teachers, not as educators, despite the fact that their university professional title presents them as Graduates in Education. Then, by showing this situation, we developed a philosophical reflection about this educational problem in the country, based on key concepts of philosophy by Friedrich Nietzsche, exposed in his book entitled The twilight of the idols. Concepts such as: nihilism, educators, will to power, amor fati or love of my destiny, aristocratic sense, the eternal return, etc., which are used in our present essay, to analyze this curious situation existing in the national teaching profession.